Clinical Evolution of New Delhi Metallo-β-Lactamase (NDM) optimizes resistance under Zn(II) Deprivation - Bahr, Guillermo (2018)
Carbapenem-resistant Enterobacteriaceae (CRE) are rapidly spreading and taking a staggering toll on all health care systems, largely due to the dissemination of genes coding for potent carbapenemases. An important family of carbapenemases are the Zn(II)-dependent β-lactamases, known as metallo-β-lactamases (MBLs). Among them, the New Delhi metallo-β-lactamase (NDM) has experienced the fastest and widest geographical spread. While other clinically important MBLs are soluble periplasmic enzymes, NDMs are lipoproteins anchored to the outer membrane in Gram-negative bacteria. This unique cellular localization endows NDMs with enhanced stability upon the Zn(II) starvation elicited by the immune system response at the sites of infection. Since the first report of NDM-1, new allelic variants (16 in total) have been identified in clinical isolates differing by a limited number of substitutions. Here, we show that these variants have evolved by accumulating mutations that enhance their stability or the Zn(II) binding affinity in vivo, overriding the most common evolutionary pressure acting on catalytic efficiency. We identified the ubiquitous substitution M154L as responsible for improving the Zn(II) binding capabilities of the NDM variants. These results also reveal that Zn(II) deprivation imposes a strict constraint on the evolution of this MBL, overriding the most common pressures acting on catalytic performance, and shed light on possible inhibitory strategies.